Spectral sensitivity and temporal resolution of the sexually dimorphic compound eyes of Electrogena lateralis - Ádám Egri; Mihály Jásdi; György Kriska (Scientific Reports)
Abstract Several mayfly species have sexually dimorphic compound eyes. Female Electrogena lateralis have uniform eyes, while male eyes are split into ventral and dorsal regions. We compared the spectral sensitivity and temporal resolution of the male eye regions and female eyes using electroretinography. Larval spectral sensitivity was also measured. Temporal resolution was quantified by measuring the eye flicker fusion frequency. The male ventral eye region and female eye were most sensitive to the green spectral range, with major and minor peak sensitivities at 536 and 366 nm, respectively. The dorsal eye region of males was exclusively ultraviolet sensitive, with maximal sensitivity at 353 nm. Relative ultraviolet sensitivity of larvae was lower than that of adults, which could be explained with the transmittance of the exuvium. Flicker fusion frequency of the male dorsal eye region was significantly higher than that of the ventral region. Temporal resolution of female eyes was similar to that of the ventral eye region of males. The high temporal resolution of the dorsal eye region and the exclusive ultraviolet sensitivity in males might play a role in the detection of females during swarming, while the female eye and the ventral male eye region may serve general navigation.